Being an end-of-life doula. (2nd July 2021) - Murphy, Sam
Abstract : This article describes what an end-of-life doula is, the training involved and how these individuals can help someone achieve the death they want, reflecting on a role that has existed traditionally in communities for centuries without formal recognition. How end-of-life doulas work holistically but also practically will be considered, outlining how keeping the dying person's preferences and wishes at the heart of their care is the primary aim. Recent issues such as advance care planning, digital legacy and Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) will be reflected on through the lens of the end-of-life doula, with the aim of encouraging open discussion and death oracy as a life skill and creating a space to make choices about the end of life. Also explored is how an end-of-life doula works within an integrative model of healthcare, working in partnership with health professionals.